2010
DOI: 10.1111/j.1365-4632.2010.04288.x
|View full text |Cite
|
Sign up to set email alerts
|

Lichen sclerosus of lips: a clinical and histopathologic study of 27 cases

Abstract: Lip LS is far less symptomatic and destructive with limited dermal sclerosis compared with genital LS. Greater awareness and histologic assessment are essential for diagnosis because of the misleading vitiligoid appearance. "Vitiligoid LS" a superficial variant proposed by Borda can be aptly applied to lip LS. Dermatologists need to be aware of this rarely reported manifestation of LS as it adds to the spectrum of oral lichenoid lesions and lichenoid dysplasia, which are suspected to have a malignant potential. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 25 publications
(44 reference statements)
0
30
1
Order By: Relevance
“…The term vitiligoid LS has since been used in a limited number of reports to describe the presentation of oral and anogenital lesions that were clinically suspected to be vitiligo given the significant depigmentation and lack of symptoms but were determined to be LS after histologic review. [2][3][4] Reports of the synchronous onset of LS and vitiligo have supported the relationship between LS and vitiligo. Three case reports describe LS and vitiligo developing concurrently but in distinct skin locations, which is probably why the term vitiligoid LS was not used and the authors instead assigned both diagnoses.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The term vitiligoid LS has since been used in a limited number of reports to describe the presentation of oral and anogenital lesions that were clinically suspected to be vitiligo given the significant depigmentation and lack of symptoms but were determined to be LS after histologic review. [2][3][4] Reports of the synchronous onset of LS and vitiligo have supported the relationship between LS and vitiligo. Three case reports describe LS and vitiligo developing concurrently but in distinct skin locations, which is probably why the term vitiligoid LS was not used and the authors instead assigned both diagnoses.…”
Section: Resultsmentioning
confidence: 93%
“…Although the term vitiligoid LS was coined in 1961, there has been recent interest in the co‐occurrence of LS and vitiligo. The term vitiligoid LS has since been used in a limited number of reports to describe the presentation of oral and anogenital lesions that were clinically suspected to be vitiligo given the significant depigmentation and lack of symptoms but were determined to be LS after histologic review . Reports of the synchronous onset of LS and vitiligo have supported the relationship between LS and vitiligo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the authors’ knowledge, there are only 39 histologically proven reported cases of OLS in the English literature. However, LS affecting the lip may be underreported . OLS is rarely symptomatic but can cause pain, soreness, pruritus, and tightness when opening the mouth .…”
Section: Introductionmentioning
confidence: 99%